Retrospective Review of Student Research Projects in a Canadian Master of Science in Physical Therapy Programme and the Perceived Impact on Advisors' Research Capacity, Education, Clinical Practice, Knowledge Translation, and Health Policy. - Lacey, Courtney; Scodras, Stephanie; Ardron, Julie; Sellan, Ryan; Garbaczewska, Martyna; O'Brien, Kelly K.; Salbach, Nancy M. (Physiotherapy Canada)
Purpose: This study's aim was to characterize the nature of students' research conducted for a Master of Science in Physical Therapy (MScPT) degree programme at a Canadian university and evaluate the lead advisors' perspectives of its impact on their research capacity, education, clinical practice, knowledge translation, and health policy. Methods: We conducted a quantitative, cross-sectional, retrospective review of research reports from 2003 to 2014 to characterize the MScPT students' research and a quantitative, cross-sectional e-survey of lead research advisors to evaluate the impact of this research. Results: Data were abstracted from reports of 201 research projects completed between 2003 and 2014. Projects were conducted primarily in university-affiliated hospitals (41.6%) or the university's physical therapy department (41.1%), and the majority (52.5%) had a clinical focus. Of the 95 lead advisors of 201 projects, 59 advisors (response rate 62.1%) of 119 projects completed the survey questionnaire. The respondents most frequently identified clinical practice (45.1%) and advisors' research capacity (31.4%) as areas positively affected by the students' research. Conclusions: The MScPT students' research projects facilitate the conduct of extensive research internally and across affiliated hospitals. This research appears to advance not only clinical practice but also the ability of lead advisors to undertake research.